VARIATIONS IN MICRONUTRIENT CONTENT IN TUBERS OF INDIAN POTATO VARIETIES - Ms, dalamu (Potato Journal, 2018)
Potato J (2017) 44 (2): 101-109 VARIATIONS IN MICRONUTRIENT CONTENT IN TUBERS OF INDIAN POTATO VARIETIES Jagdev Sharma1 , Dalamu2 , V Sharma1 , VK Dua1 , VK Gupta3 and Dipak Kumar1 ABSTRACT: The objective of the present study was to determine genotypic variations in mineral content of the Indian potato varieties and thereby defines the way forward for breeding nutrient rich potato varieties. Considerable variations were observed in metal (Fe, Zn, Mn, Cu) concentrations in the 48 potato varieties under uniform management practices and non nutrient limited conditions with average yield levels ranging from 22.15 to 43.23 t/ha. Iron concentration in tuber flesh varied from 19.96 to 49.51 mg/kg, zinc from 12.59 to 22.85 mg/kg, manganese from 14.19-29.86 mg/kg, and copper from 5.13 to 21.06 mg/kg. The accumulation pattern of the metal on the basis of total content in tuber flesh and peel was in the order Fe> Mn> Zn> Cu. Average proportion of mineral content in tuber flesh was in the order of Zn (87.14%) > Cu (84.64%) > Mn (78.29%) > Fe (60.13%). Losses due to peeling are highest for Fe (39.87%) ranging from 24.10 to 53.83% in different varieties. The tuber yield did not show any significant correlation with tuber mineral content. Keeping in view large seasonal variations in mineral content in peel and significant loss of minerals like Fe during peeling process, strategies to increase the mineral content (micronutrient rich) potatoes should focus on improving their content in tuber flesh.